CAUSAL FACTORS AND INTERVENTIONS TO PREVENT HYPERTENSION IN RURAL AREA: LITERATURE REVIEW - Tantut Susanto; Zaiful Rahman; Rondhianto Rondhianto (UNEJ e-Proceeding, 2023)
Background: Hypertension is a non-communicable disease known as The Silent disease. Preavlesni Hypertension in rural areas and in cities has a relatively small comparison number. The factors that cause hypertension in rural areas are different from the factors that cause hypertension in urban areas. The physical activity lifestyle of individuals with hypertension who live in rural areas has a higher life expectancy than individuals with hypertension in urban areas. Hypertension intervention is included in one of the SDGs programs. aims to provide an overview of the factors that cause hypertension and interventions carried out to treat hypertension in rural areas. Methods: scoping review is used with the PRISMA approach. Electronic databases were used such as PubMed, Google Scholar, and Science Direct. A literature review was conducted on international journals published in the last 5 years, available in full text and not the result of a review. Result : This study concludes that the causes of hypertension in rural areas include: alcohol use, occupation, smoking habits, age, zinc intake, sleep duration, exposure intensity to the use of biomass fuels, pesticides, and obesity. Interventions that can be given to people with hypertension who live in rural areas include: physical activity, family support, self-screening for routine blood pressure control, and improving sleep quality. Conclusions: In providing hypertension prevention interventions to people in rural areas, door-to-door visits are also needed to evaluate the success of the interventions that have been given, as well as seek information related to the causal factors that are obstacles to the success of the interventions that have been given Keywords: Hypertension in Rural areas, Hypertension intervention